2018
DOI: 10.5539/jas.v10n9p6
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation and Soil Texture Effects on Yield and Yield Components of Mungbean

Abstract: Mungbean [Vigna radiata (L.) Wilczek] is a short-duration and relatively drought-tolerant crop grown predominantly in the tropics. This grain legume can improve soil fertility through biological nitrogen (N) fixation. To assess the effects of Bradyrhizobium (group I) inoculation on yield and yield attributes of mungbean, a greenhouse study was conducted during Fall 2016 with two mungbean cultivars (‘Berken’ and ‘OK2000’), two inoculum treatments (inoculated and uninoculated), and two soil textures (loamy sand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…A greater shoot and total plant dry matter of mungbean grown on the silt loam soil, exceeding by more than 150% those on the loamy sand soil texture, was likely a result of enhanced fertility and greater water holding capacity on the silt loam soil. A previous study conducted by Diatta et al (2018) also reported that mungbean grown on a silt loam soil produced 40% more biomass than on a loamy sand soil. Mungbean grown on the silt loam soil also recorded the highest amounts of shoot δ 15 N (9.12‰).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A greater shoot and total plant dry matter of mungbean grown on the silt loam soil, exceeding by more than 150% those on the loamy sand soil texture, was likely a result of enhanced fertility and greater water holding capacity on the silt loam soil. A previous study conducted by Diatta et al (2018) also reported that mungbean grown on a silt loam soil produced 40% more biomass than on a loamy sand soil. Mungbean grown on the silt loam soil also recorded the highest amounts of shoot δ 15 N (9.12‰).…”
Section: Discussionmentioning
confidence: 70%
“…In mungbean, N is exported in the form of ureide, a nitrogenous transport compound, from the nodules (Crews et al 2004;Herridge and Peoples 2002). Limited production in regions other than South and Southeast Asia, Australia, and East Africa (Diatta et al 2018;Keatinge et al 2011) has resulted in scant research efforts aiming to understand the observed variation in N 2 fixation by mungbean and assess its contribution to cropping system (Herridge et al 2008;Raji et al 2019;Thilakarathna et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though N 2 fixation in mungbean was not measured in the present study, we observed nodulation and hypothesized that inoculation of mungbean may have led to increased N 2 fixation and N inputs. The greenhouse study evaluating the effects of inoculation on mungbean yield showed that inoculated plants had higher number of root nodules, seed weight, and plant biomass than uninoculated mungbean (Diatta et al., 2018). Similar to Trail et al.…”
Section: Discussionmentioning
confidence: 99%
“…The use of biofertilizers in pulse crop production can be a cost-effective and environmentally friendly alternative to synthetic fertilizer production [7]. Some factors affecting proper nodulation include, soil acidity, the water holding capacity of the soil, and soil texture [8,9]. Soil transfer, or residual indigenous rhizobium, is largely considered to be the first method of legume inoculation and early experiments of exogenous soil inoculation saw yields 10 times that of the control [10].…”
Section: Introductionmentioning
confidence: 99%